Molecular epidemiology of Burkholderia pseudomallei and its relatives - Chan, Mark Boon Pho (Nanyang Technological University, 2023)
Burkholderia pseudomallei, the causative agent of melioidosis, is endemic to Southeast Asia and Northern Australia. In Singapore, 1,736 melioidosis cases have been reported since 1989, with an overall case fatality rate of 19%. This study aims to study the genomic epidemiology of B. pseudomallei complex (BPC) and B. cepacia complex (BCC) in Singapore soils. We have d eveloped a direct soil qPCR assay to map the distribution of B. pseudomallei and B. thailandensis in a local park and report the first isolation of B. thailandensis in Singapore. We explored the genomic diversity of local B. pseudomallei (n = 14) and B. thailandensis (n = 2) by characterizing mobile genetic elements (MGEs) such as bacteriophages, plasmids, genomic islands, and insertion sequences. We found evidence of novel plasmids harbouring heavy metal resistance genes, expanding the survival gene repertoire of these species. Pangenome analysis of Singapore B. pseudomallei (n = 100) showed the presence of clade-specific CRISPR arrays and plasmids. Furthermore, we explored the role of recombination in maintaining local B. pseudomallei population diversity and observed high sequence variations in genomic regions responsible for virulence. Together, our results demonstrate the genome plasticity of the BPC and the roles MGEs play to drive the evolution of these species.